AUTO-EVALUATION OF UNIVERSITY TEACHER AS A BASIS FOR QUALITY AND PROFESSIONALISM IN THE UNIVERSITY EDUCATION - Huľová, Zlatica (European Scientific Journal, ESJ, 2014)
The author of the submission studies some general patterns in the transformation processes and the processes of internationalization in the higher education, which started with the adoption of Bologna Declaration and the Lisbon Strategy. The author pointed out the quality and professionalism of higher education as well as the opportunities for improving its quality, which are currently the most pressing issues concerning a teaching profession. The results of the questionnaire survey, which was carried out in 2009, 2010 and 2011 and in which 114 future pre-primary and primary school teachers participated, form part of the university teacher’s auto evaluation. The auto evaluation is one of the elements that determine the improved quality of higher education and enhanced professional competencies of future pre-primary and primary school teachers. The aim of the survey was to gather opinions on the quality of higher education and on the educational needs of students in the field of Pre-school and elementary pedagogy. The survey became the starting point for solving of the research task1.